2020
DOI: 10.1002/ehf2.12916
|View full text |Cite
|
Sign up to set email alerts
|

The detrimental effect of COVID‐19 nationwide quarantine on accelerometer‐assessed physical activity of heart failure patients

Abstract: Aims A reduction of habitual physical activity due to prolonged COVID-19 quarantine can have serious consequences for patients with cardiovascular diseases, such as heart failure. This study aimed to explore the effect of COVID-19 nationwide quarantine on accelerometer-assessed physical activity of heart failure patients. Methods and results We analysed the daily number of steps in 26 heart failure patients during a 6-week period that included 3 weeks immediately preceding the onset of the quarantine and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 18 publications
(35 reference statements)
7
61
1
1
Order By: Relevance
“…This was accompanied by an increase in sitting time by 276 minutes per week, an adverse finding given the adverse health impacts associated with increased sedentary and sitting time. 20 These findings correlate with other studies from the UK (a decrease in 25% of adults aged over 20 years following lockdown), 21 Spain 22 and China, 23 and from a global survey collected in 8 different languages, 24 despite the differences in outdoor exercise permissions between countries. Reductions in PA may impact disproportionately across society.…”
Section: Discussionsupporting
confidence: 86%
“…This was accompanied by an increase in sitting time by 276 minutes per week, an adverse finding given the adverse health impacts associated with increased sedentary and sitting time. 20 These findings correlate with other studies from the UK (a decrease in 25% of adults aged over 20 years following lockdown), 21 Spain 22 and China, 23 and from a global survey collected in 8 different languages, 24 despite the differences in outdoor exercise permissions between countries. Reductions in PA may impact disproportionately across society.…”
Section: Discussionsupporting
confidence: 86%
“…Thirteen studies examined populations with medical conditions for which all but one study, 80 used subjective measurements of PA change, and in only 6/12 were these previously validated measurement tools. Regarding the types of changes reported, nine studies 23 26 36 40 43 44 72 80 86 reported changes in time spent in PA, all reporting decreases in PA time.…”
Section: Resultsmentioning
confidence: 99%
“…This reduction in physical activity could be explained by the fact that moderately or highly physically active participants usually performed their exercises in training groups, fitness centers, and sports clubs, that were temporarily closed during the lockdown ( Constandt et al, 2020 ). Further reasons could be less time, the lack of a competitive element in the training or being at risk for developing COVID-19 ( Constandt et al, 2020 ; Di Stefano et al, 2020 ; Ruiz-Roso et al, 2020 ; Vetrovsky et al, 2020 ). Interestingly, 33% of inactive participants were reported to be more active during the lockdown in Canada ( Lesser and Nienhuis, 2020 ), while this was the case for as many as 55% ( n = 12 out of 22) in our study on Swiss office workers.…”
Section: Discussionmentioning
confidence: 99%
“…A Belgian study came to a similar conclusion and showed that physically active adults, who normally exercised in a group setting and did not use online training tools during social distancing, were less active than before ( Constandt et al, 2020 ). The same applied to many patients with type 2 diabetes mellitus, heart failure, cystic fibrosis, or neuromuscular diseases, who experienced increasing physical inactivity during home confinement ( Di Stefano et al, 2020 ; Radtke et al, 2020 ; Ruiz-Roso et al, 2020 ; Vetrovsky et al, 2020 ). Two large surveys also showed that the lockdown had a negative effect on physical activity levels ( Ammar et al, 2020 ; Qin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%